High-shear granulation of hygroscopic probiotic-encapsulated skim milk powder: effects of moisture-activation and resistant maltodextrin - Letona, Andres (2023)
A fine, hygroscopic, and poorly flowable probiotic powder encapsulating Lactobacillus rhamnosus GG (LGG) was granulated using a high-shear granulation process, wherein a small amount of water (4%, w/w) was used for moisture-activation with or without 10% (w/w) resistant maltodextrin (RM). The process consisted of four steps; premixing, agglomeration, moisture absorption, and drying steps. The moisture content, water activity, and viable cell count were monitored during the granulation. The size, morphology, and flowability of the granules were determined. The powder was successfully converted to about 10-times-larger granules (mass mean diameter = 162-204 µm) by this process, and the granules had a 'snowball' morphology. The LGG cells were well preserved under the high-shear granulation conditions, and the viable cell count of the granules greatly exceeded the minimum therapeutic level recommended for probiotic powders. The addition of RM decreased the moisture content of the granules; improved cell resistance to drying stress; narrowed the particle size distribution, with reductions seen in both very fine and very large particles; and produced more flowable granules. Moisture sorption analysis and differential scanning calorimetry demonstrated that these positive effects of RM on granulation were primarily attributed to its water distribution ability rather than its glass transition-related binding ability.